The benefit of top soil and fertilizer mixture to improve the ex-coal mining land - SOPIALENA SOPIALENA; ROSFIANSYAH ROSFIANSYAH; SURYA SILA (Smujo International, 2017)
Sopialena, Rosfiansyah, Sila S. 2017. The benefit of top soil and fertilizer mixture to improve the ex-coal mining land. Nusantara Bioscience 9: 36-43. The mining activities have led severe impacts on some environmental issues including a decrease in soil fertility, which affects the ability of soil to supply soil nutrients to growing plants, a destruction in soil structure, and the loss of microorganisms, which are important for reforming process to treat organic materials. In this regards, reclamation of mined degraded land has been continually used to improve soil structure and its microorganisms. In practice, for large scale reclamation, fertilizer use can primarily enhance soil qualities in improving plant’s growth and yield. It is suggested that healthy soil should contain millions of microorganisms at the aggregation which leads to the improvement of soil nutrients and its structure, as the medium for plant growth. For this purpose, therefore, this study aimed to determine the impact of organic fertilizer (Ostindo) and top soil mixture on microbial diversity, soil fertility and the growth of sengon (Paraserianthes falcataria L. Nielsen). This study made use of a randomized block design, using four treatments and five replications including P0: without top soil and fertilizer, P1: with top soil but without fertilizer, P2: without top soil but with fertilizer, P3: mixture of top soil and fertilizer. The results showed that a mixture of top soil and fertilizer has successfully increased in the number of fungal genus, starting from two genus (Phytium and Penicillium) turning into five genus (Phytium, Fusarium, Penicillium, Aspergillus, and Rhizoctonia), as well as in the number of nematode genus, from two (Dorylaimus and Rhabditis) turning into five genus (Dorylaimus, Steinernema, Dorylaimus, Hoplolaimus, and Mononchus). This study indicated that the mixture has significantly improved soil health in ex-coal mining land, which was viable through the pH level (almost neutral), the significant increase of C, N and P2O5 , and also the growth of Sengon. In conclusion, this study succeeds in demonstrating that the mixture of top soil and fertilizer has enhanced the microbial diversity, soil fertility, and sengon growth.